2020
DOI: 10.1037/tra0000649
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for warriors: An intervention for veterans with comorbid chronic pain and PTSD.

Abstract: Objective: Comorbid chronic pain and posttraumatic stress disorder (PTSD) is common in veterans; this comorbidity is associated with increased severity and poorer prognosis when compared to each outcome alone. Yoga has been shown to be effective for chronic pain and promising for PTSD, but yoga for comorbid pain and PTSD has not been examined. This article offers empirical support for a yoga intervention for comorbid chronic pain and PTSD in a veteran population. Method: Results are presented from a 4-year pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…25 In a study with 34 veterans, Chopin and colleagues found that a trauma-informed yoga intervention was associated with a statistically significant reduction in PTSD symptoms, as did a study by Zaccari and colleagues with 17 veterans. 26,29 Justice and Brems also found some evidence that trauma-informed yoga interventions helped PTSD symptoms in a small sample of 4 veterans, although these results were not quantitatively analyzed. 27 In contrast, a small pilot study (n = 12) by Staples and colleagues testing a biweekly, 6-week yoga program did not show a significant effect on PTSD symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In a study with 34 veterans, Chopin and colleagues found that a trauma-informed yoga intervention was associated with a statistically significant reduction in PTSD symptoms, as did a study by Zaccari and colleagues with 17 veterans. 26,29 Justice and Brems also found some evidence that trauma-informed yoga interventions helped PTSD symptoms in a small sample of 4 veterans, although these results were not quantitatively analyzed. 27 In contrast, a small pilot study (n = 12) by Staples and colleagues testing a biweekly, 6-week yoga program did not show a significant effect on PTSD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…18,[25][26][27][28][29] Participants consisted of veterans with chronic pain, post-9/11 veterans, female veterans of childbearing age, veterans with a history of trauma therapy, and other veterans. Types of exercise included moderate aerobic exercise and yoga.…”
mentioning
confidence: 99%
“…18 It may also be useful to offer yoga interventions taught by older veterans, such as in Veteranto-Veteran programs, and veteran-specific resources available through VHA Whole Health program. 24,26,27 Researchers should consider interventions that address investigator reluctance to include older adults in clinical trials, including comorbidities, ageism, and practical barriers. 39 These considerations may be especially applicable now that research on the efficacy of yoga has matured and effectiveness studies are now needed.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Yoga has been increasingly studied within the Veterans Health Administration (VHA) for treatment of posttraumatic stress disorder (PTSD) and has been found effective in reducing symptoms through the use of traumainformed and military-relevant instruction as well as a military veteran yoga teacher. [24][25][26] This work has not targeted older veterans or cancer survivors who may be more difficult to recruit into such programs, but who would nevertheless benefit.…”
mentioning
confidence: 99%
“…This study's preliminary results add to the growing empirical evidence on TIWT as a complementary treatment for youth with trauma histories. Chopin et al (2020) present the results of a 4-year pilot study, examining the use of yoga for comorbid chronic pain and PTSD symptoms in veterans. Their study is the first research study to consider the effects of yoga on individuals presenting both chronic pain and PTSD simultaneously.…”
Section: Special Issue Goals and Articlesmentioning
confidence: 99%